2020
DOI: 10.1371/journal.pone.0238736
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of laser-captured crown root primordia reveals new pathways activated during early stages of crown root formation in rice

Abstract: Crown roots constitute the main part of the rice root system. Several key genes involved in crown root initiation and development have been identified by functional genomics approaches. Nevertheless, these approaches are impaired by functional redundancy and mutant lethality. To overcome these limitations, organ targeted transcriptome analysis can help to identify genes involved in crown root formation and early development. In this study, we generated an atlas of genes expressed in developing crown root primo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Identification of light-induced lncRNAs antisense to ERF99 , B-type response regulator genic region may play a role in its transcriptional regulation. ERF99 is known to modulate root architecture and downregulated in crown root primordia 95 . MADS27 gene targeted by lncRNAs present in both dark and light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of light-induced lncRNAs antisense to ERF99 , B-type response regulator genic region may play a role in its transcriptional regulation. ERF99 is known to modulate root architecture and downregulated in crown root primordia 95 . MADS27 gene targeted by lncRNAs present in both dark and light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OsPLT5, in combination with the WUS2 gene, promotes regeneration from tissue culture, suggesting that they function as pluripotency factors in grass species, including O. sativa (Lowe et al, 2016). Expression profiling in rice roots of OsPLT1∼6 revealed that these genes are up-regulated both in the primordia of CRs and in developing CRs (Garg et al, 2020;Lavarenne et al, 2020). Moreover, these euANT/PLT clade A genes are specifically expressed in different sectors of the CR meristem (Li and Xue, 2011;Kitomi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, euANT/PLT clade B genes including OsPLT8/CRL5 might play a key role during CR initiation without being involved in the later steps of CR primordia differentiation (Garg et al, 2020;Lavarenne et al, 2020). In this sense, OsPLT8/CRL5 was initially demonstrated to be involved in the auxin-dependent de novo pathway of CR initiation in rice, through the repression of cytokinin signaling by positively regulating the type-A RR OsRR1 (Kitomi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%